Nurses perspectives on healthcare errors in oncology care: A cross-sectional study. (April 2020) - Waller, Amy; Turon, Heidi; Bryant, Jamie; Shepherd, Jan; Hobden, Bree; Sanson-Fisher, Rob
Abstract: Purpose: Recognition and responses of the health system to healthcare errors are key areas for improvement in oncology. Despite their role in direct patient care, nurses' perceptions of errors have rarely been explored. The aim of this study was to determine oncology nurses' direct experience of healthcare errors in the previous six months; the circumstances surrounding the error; and ensuing actions by the healthcare system. Methods: Cross-sectional survey of nurses who were members of an oncology nursing society and/or registered or enrolled nurses employed in an oncology setting. Participants indicated whether they had direct experience ( i.e . direct involvement or witnessing ) of error(s) in the previous six months. Those who experienced an error indicated their perceptions of the: cause; location and phase of care; how the error was identified, who was responsible, level of harm and action(s) taken. Results: 67% (n = 65/97) of nurses who completed the survey had direct experience with at least one error in the previous six months. According to these nurses, most occurred during treatment (n = 48, 74%), happened in outpatient clinics (n = 28, 43%) and were related to chemotherapy (n = 15, 23%). Nurses perceived errors were primarily caused by nurses (n = 36, 55%) and doctors (n = 27, 42%); and 54% (n = 35) were deemed 'near-miss'. Nurses perceived errors were recorded (n = 40, 62%), explained to patients (n = 33, 51%) and an apology provided (n = 32, 49%). Conclusion: Two-thirds of oncology nurses in this study had direct experience with an error in the previous six months. Nurses perceived response to errors as inconsistent with open disclosure standards. Strategies to improve accuracy of measures of error and response of the health system, including adherence to open disclosure processes, are required. Highlights: Two thirds of oncology nurses reported direct experience with a healthcare error in the past six months. Health system responses to disclosure of errors was inconsistent. There is scope to improve adherence to open disclosure practices.